2014
DOI: 10.1371/journal.pone.0090135
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Proteinuria Associated with Vascular Endothelial Growth Factor Receptor Tyrosine Kinase Inhibitors in Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: BackgroundVascular endothelial growth factor tyrosine-kinase inhibitors (VEGFR-TKIs) have emerged as an effective targeted therapy in the treatment of cancer patients, the overall incidence and risk of proteinuria associated these drugs is unclear. We performed a systematic review and meta-analysis of published clinical trials to quantify the incidence and risk of proteinuria associated with VEGFR-TKIs.MethodologyDatabases from PubMed, Web of Science and abstracts presented at ASCO meeting up to May 31, 2013 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 81 publications
1
49
0
Order By: Relevance
“…However, VEGF plays multiple roles in physiologic processes, and thus its inhibition could have potentially serious systemic consequences. Although previous researches have shown that anti-VEGFR agents significantly increases the risk of developing anti-VEGF adverse events, including hypertension, [3941] hemorrhage, [42,43] proteinuria, [44,45] gastrointestinal perforation, [46] congestive heart failure, [4749] and thromboembolic events. [5053] , the risk of these adverse events in advanced NSCLC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, VEGF plays multiple roles in physiologic processes, and thus its inhibition could have potentially serious systemic consequences. Although previous researches have shown that anti-VEGFR agents significantly increases the risk of developing anti-VEGF adverse events, including hypertension, [3941] hemorrhage, [42,43] proteinuria, [44,45] gastrointestinal perforation, [46] congestive heart failure, [4749] and thromboembolic events. [5053] , the risk of these adverse events in advanced NSCLC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Two to ten percent of this event fulfilled G3 criteria according to common terminology criteria for adverse events [42,45,47]. Total risk of all grade proteinuria assessed by meta-analysis, published by Zhang et al, was 11.6% for sorafenib compared with 13.5 and 10.0% for pazopanib and vandetanib, respectively [54].…”
Section: Treatment-related Toxicitymentioning
confidence: 96%
“…Hypertension, proteinuria, gastrointestinal perforation, thrombosis and CHF belong to possible VEGF inhibitionrelated consequences [52][53][54][55][56][57]. Keizer et al constructed a pharmacokinetic-pharmacodynamics (PK-PD) model for hypertension and proteinuria applied in patients who were given lenvatinib.…”
Section: Treatment-related Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some adverse effects are shared with conventional chemotherapeutic agents while others are unique and not typically observed with cytotoxic drugs. Specific toxicities associated with VEGF axis inhibition using VEGF‐ligand or VEGFR inhibitors include cardiovascular effects (hypertension, thromboembolism, left ventricular dysfunction, cerebrovascular effects) as well as noncardiovascular effects (proteinuria, bleeding/hemorrhage, delayed wound healing, gastrointestinal perforation, fatigue, and dysphonia) . Other rare class effects of VEGF axis inhibition comprise reversible posterior leukoencephalopathy (RPLS), osteonecrosis of the jaw (ONJ), and microangiopathic hemolysis.…”
Section: Angiogenesis In Practice: Clinical Implicationsmentioning
confidence: 99%